ANTHROPOMORPHIC IMAGES OF MASCARONS IN LVIV ARCHITECTURAL AND DECORATIVE PLASTIC ART OF THE XIX – EARLY XX CENTURIES - Кукіль, Л. Л. (Art and Design, 2020)
The purpose of the study is to analyze the information load and plastic solutions of the anthropomorphic mascarons on the facades of Lviv buildings of the XIX – early XX centuries. Methodology. The article uses general scientific research methods: the historical and comparative method; the method of synthesis and the art history analysis. Research results. The Lviv architectural and decorative plastics of the 19th and early 20th century is characterized by a widespread typology of the mascarons on the facades of the buildings. Various types of faces of old Lviv street, paired male and female images, which represent the unity and the harmony of two beginnings (portraits of married couples), as well as the generalized artistic images, belong to the number of the anthropomorphic maskarons of Lviv of the specified period. The article analyzes the information load and the plastic-stylistic features of various anthropomorphic maskarons of the typological group under study. The authors of the various types of old Lviv street emphasized the efforts to convey the character of the depicted faces. Their artistic expression is enhanced by some personal attributes. This applies to the paired and the generic Lviv maskarons to a lesser extent. On the basis of an art historical analysis of a number of specific samples of the anthropomorphic mascarons of Lviv of the 19th and early 20th century, a species classification of the given typological group has been developed. Scientific novelty. Detected and analyzed the information load and plastic characteristics peculiarities of the mascarons in Lviv architectural and decorative sculpture of the XIX – early XX centuries. Practical ignificance. The proposed article is part of a comprehensive study of the broad typology of the Lviv maskarons of the 19th and early 20th century. The results of the work open up some opportunities for a further research of the groups and the subgroups of the Lviv mascarons and for a detailed art historical analysis of some individual original samples of relief faces of Lviv of the studied period.